HDI XMAS July 15, 2019. Dorothy Reid photos. - Barrett, Terra
A photo of a band playing their instruments. Stan Reid playing the trumpet, Calvin Legge sitting, unknown person, Curtis Chislett (baritone), Judy Reid (in red), and Lori Reid (far right).